Reglamentación a las actuaciones de las y los inspectores de trabajo. - Vivas Barrios, Xesenia Giovanna (2015)
This research which focus is Regulation to the Performances of the Labor Inspectors, is total interest, because it is highly relevant and of a purely legal problem. Its content, explains how the Ministry of labor, through the management and labor, has administrative powers, which are not met fully, leaving vulnerable workers. This provision gives the full authority to act, through work inspectors, in protection of people with worker or employer status and who’s working relationship they are regulated by the provisions of the labor code.